Chemotaxis and Shorter O-Antigen Chain Length Contribute to the Strong Desiccation Tolerance of a Food-Isolated Cronobacter sakazakii Strain - Qian, Chengqian; Huang, Min; Du, Yuhui; Song, Jingjie; Mu, Huiqian; Wei, Yi; Zhang, Si; Yin, Zhiqiu; Yuan, Chao; Liu, Bin; Liu, Bin (Frontiers in Microbiology, 2022)
Cronobacter sakazakii is an opportunistic pathogen causing a lethality rate as high as 80% in infants. Desiccation tolerance ensures its survival in powdered infant formula (PIF) and contributes to the increased exposure to neonates, resulting in neonatal meningitis, septicemia, and necrotizing enterocolitis. This study showed that a food-isolated C. sakazakii G4023 strain exhibited a stronger desiccation tolerance than C. sakazakii ATCC 29544 strain. Considering the proven pathogenicity of G4023, it could be a big threat to infants. Transcriptome and proteome were performed to provide new insights into the desiccation adaptation mechanisms of G4023. Integrated analyses of these omics suggested that 331 genes were found regulated at both transcriptional and protein levels (≥2.0- and ≥1.5-fold, respectively). Deletion of chemotaxis system encoded genes cheA and cheW resulted in decreased tolerance in both short- and long-term desiccation. Reduced O-antigen chain length contributed to the biofilm formation and desiccation tolerance in the short term rather than the long term. In addition, biosynthesis of flagella, arginine and its transport system, and Fe/S cluster were also observed regulated in desiccated G4023. A better understanding of desiccation adaptation mechanisms of G4023 could in turn guide the operations during production and preservation of PIF or other food to reduce survival odds of G4023 and lower its exposure to get to infants.